When sorrow comes : the power of sermons from Pearl Harbor to Black Lives Matter - Matthes, Melissa M., 1964- (Harvard University Press, 2021)
"When Sorrow Comes explores the sermons that American clergy, primarily Protestant ministers, gave in the first weeks after national crises, beginning with Pearl Harbor. Additional chapters include the sermons given after the assassinations of John F. Kennedy and Martin Luther King Jr.; those given after the Oklahoma City bombing and the LA "Race Riots"; a chapter on the sermons given in the immediate aftermath of September 11, 2001; and a final chapter on the killing of Trayvon Martin and the Newtown School Shooting. The book focuses on three broad analytic questions: How do the sermons understand the tragedy and recommend that listeners process their grief? What assumptions inform the clergy's narratives of the relation between church and state during the crisis? What are the meanings ascribed to being both a Christian and a citizen during each emergency?"--